Pendampingan Kegiatan Keagamaan pada Masyarakat Dusun Airport - Sitti Aisyah; Sundari Sundari; Hendra Bata; Ramdanil Mubarok (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
The enthusiasm of the community to attend religious activities, such as the taklim assembly, tabligh akbar, the celebration of Islamic holidays, yasinan and tahlilan tends to be lacking. However, it is often found that community participation tends to increase when attending music concerts, art performances, night markets, and activities that are far from religious values. The purpose of this service is to increase community participation in participating in religious activities at Dusun Airport. The method used in this service is the Participatory Action Research method, where the author is directly involved in its implementation. The result is assistance for religious activities in the form of teaching at the TPA Nur Hijrah Mosque, the celebration of the Isra' Mi'raj of the Prophet Muhammad SAW, and recitation of the taklim assembly. Assistance for religious activities in the airport hamlet can increase the knowledge and experience of the community in the religious field within a framework of togetherness. This can be seen from the increasing attention of parents towards their children's Al-Qur'an education, the spirit of togetherness in participating in taklim assemblies is increasing, and the commemoration of the Isra' Mi'raj is the forerunner to the celebration of other big days in one calendar year Hijri.